Converting the Words of God: An experimental evaluation of stylistic choices in the new Dutch Bible translation - Renkema, Jan; van Wijk, Carel (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2021)
In an experiment stylistic choices in the new Dutch Bible translation were evaluated. 185 participants evaluated 4 fragments which differed in type of variation (lexical or syntactic), source of the fragment (Bible - classical text) and the way the variations were applied (single - mixed). Also the religious¬ness of the evaluator was taken into account. Examined is whether lexical modernization and syntactic simplification are evaluated the same, whether single variations show a better insight into the evaluations and if the evaluation is influenced by the source of the text or the religiousness of the evaluator. The results showed that there is a difference in evaluation between syntactic and lexical variation, that single variation gives better insight into the evaluations and that source of the text and religiousness do not influence the evaluations. This study demonstrates that translators must involve readers at an early stage in their discussions on a required or appropriate register.